STRATEGI PENGEMBANGAN DESA WISATA SETULANG, KECAMATAN MALINAU SELATAN, KABUPATEN MALINAU, KALIMANTAN UTARA - I Wayan Ruspendi Junaedi; Titin Veronika; Irawan Irawan; Gede Nyoman Wiratanaya (JEMBA : Jurnal Ekonomi Pembangunan, Manajemen dan bisnis, Akuntansi, 2022)
Village tourism the one of strategy to solve the problem of poverty in the village. Constraints such as infrastructure are still lacking and information about Setulang Tourism Village is still limited yet, this research was conducted to find out the development strategies that exist at Setulang Tourism Village. There are 3 respondents of the SWOT analysis, techniques to getting data by interviewing, documenting and filling out the questionnaires. There are 4A internal variables, accessibility, the distance of location and transportation facilities, attractions, namely arts and cultural activities, the pure of forest and handicrafts, ancillary namely local organizations and government, and amenities, which are available of homestays. External variables are socio-cultural, competition, law, economy, security and threats. 9 indicators of internal variable,there are 2 weaknesses namely community handicrafts and transportation facilities. 10 indicators of external variable there are two threats, namely same of tourist attractions and the convenience of tourists to visiting. In the SWOT analysis there are IE, IFAS / EFAS, and SWOT matrix. IFAS results obtained 3.22 while the number of EFAS 2.97. Matrix of IE, Setulang Tourism Village in 2018 is high or strong. This research shows several indicators that Setulang Tourism Village needs to improve to become a tourist destination and hopefully it can be an advice for the future. Keywords : Definition of Tourism Village, Sample Determination Method, SWOT Analysis